The antecedents for homelessness in Bukit Bintang, Kuala Lumpur, Malaysia / Mohd Ramlan Mohd Arshad...[et al.] - Mohd Arshad, Mohd Ramlan; Madzlan, Nurul Fatin; Mawi, Nurhafizah; Rabun, Mohd Nazir (Universiti Teknologi MARA, Kedah, 2019)
The aim of this study is to explore the antecedents for homelessness in Bukit Bintang with the main objectives of exploring the relationship between the variables namely poverty, unemployment, domestic violence and addiction towards homelessness in Bukit Bintang, Kuala Lumpur. 150 respondents of this study are community that become homeless that get shelter in the roadside of Bukit Bintang, Kuala Lumpur, Malaysia. Purposive sampling technique was used with questionnaire as the instrument. Correlation and regression analysis were conducted, and the findings show that there are significant relationships between the variables and homelessness with domestic violence as the main factor. Hence, various parties such as authority, non-governmental bodies and community has benefited from the study.